2018
DOI: 10.2166/wst.2018.143
|View full text |Cite
|
Sign up to set email alerts
|

Low-dissolved-oxygen nitrification in tropical sewage: an investigation on potential, performance and functional microbial community

Abstract: Intensive aeration for nitrification is a major energy consumer in sewage treatment plants (STPs). Low-dissolved-oxygen (low-DO) nitrification has the potential to lower the aeration demand. However, the applicability of low-DO nitrification in the tropical climate is not well-understood. In this study, the potential of low-DO nitrification in tropical setting was first examined using batch kinetic experiments. Subsequently, the performance of low-DO nitrification was investigated in a laboratory-scale sequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Our modeling study provided a kinetic data to support the high proportional abundance of Nitrospira and comammox commonly observed in low-DO reactors below 1 mg O2 L -1 treating low-strength tropical wastewater [9,20]. Through the proliferation of K-strategist nitrifiers under low-DO condition (< 1 mg O2 L -1 ), WWTPs treating low COD/N wastewater may successfully operate a low-DO nitrification process to encourage energy saving between 23% and 25% [8,14].…”
Section: Implications On the Design Of Wastewater Treatment Plantsmentioning
confidence: 65%
See 2 more Smart Citations
“…Our modeling study provided a kinetic data to support the high proportional abundance of Nitrospira and comammox commonly observed in low-DO reactors below 1 mg O2 L -1 treating low-strength tropical wastewater [9,20]. Through the proliferation of K-strategist nitrifiers under low-DO condition (< 1 mg O2 L -1 ), WWTPs treating low COD/N wastewater may successfully operate a low-DO nitrification process to encourage energy saving between 23% and 25% [8,14].…”
Section: Implications On the Design Of Wastewater Treatment Plantsmentioning
confidence: 65%
“…To improve the existing process, How et al [8] and Cao et al [9] showed that efficient low-DO nitrification below 1 mg L -1 was feasible for tropical wastewater by capitalizing on the warm wastewater temperature (30 ± 1ºC) to promote the growth of slow-growing…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When DO concentrations are high, it may lead to low denitrification rates due to the reduction of anoxic zones. How et al (2018) reported low COD concentration in sewage may have contributed to active nitrification in low DO conditions by minimizing oxygen competition between heterotrophs and nitrifiers. At low DO concentrations, the microbial community structure of the nitrifying sludge is expected to be different from a standard high DO nitrifying community.…”
Section: Reduction Efficiency Of Ammonia-nitrogen Without Pva Gel-beadsmentioning
confidence: 98%
“…The ability of nitrifying microorganisms to oxidize N-NH 4 and N-NO 2 has been widely used in biological wastewater treatment (Semenova et al, 2012, Gnida et al, 2016. Biological nitrification as a large-scale biotechnology is used as the final stage of wastewater treatment, when the treated water containing nitrates can be discharged into the reservoir, and in modern technologies for deep purification of nitrogen compounds -as an intermediate stage when it is combined with subsequent biological denitrification (Haandel et al, 2012, How et al, 2018. Modern urban wastewater treatment schemes use sludge liquid recycling in two-, three-, four-and five-stage processes that allow deep purification of not only nitrogen compounds but also other biogenic elements.…”
Section: Introductionmentioning
confidence: 99%